Patch and landscape responses of bird abundance to fragmentation in agroecosystems of east-central Argentina - Calamari, Noelia Cecilia (2018)
Forest fragmentation in agroecosystems is linked to declines of avian species worldwide. Agriculture has greatly reduced native forest cover in east-central Argentina. Assessing the influence of fragmentation on forest bird populations is vital to inform reliable conservation and management strategies for the Espinal region of Argentina. We determined the relationships of vegetation structure within native forest patches, size and shape of these patches (patch scale), composition and spatial configuration (at landscape scale) to relative abundance of 17 forest bird species during austral fall-winter and spring-summer seasons. Birds were sampled from 2007–2009 in 45 forest patches within three landscape mosaics (30 x 30 km) representing a gradient of native forest fragmentation in east-central Argentina. We used an information-theoretic approach and approximated model inference to examine the effect of predictor environmental variables at two spatial scales on patterns of forest bird abundance. Density of trees within forest patches was the main predictor of bird abundance at the patch scale. Amount of forest and spatial configuration were also important. The abundance of several bird species was greater in patches with high density of trees and landscapes characterized by more forest cover and larger patches in close proximity. We found two main avian response patterns to forest fragmentation and patch characteristics. This information contributes reliable knowledge for the design of conservation measures of agricultural landscapes in the Espinal region of Argentina.